Reliability Assessment Of Reinforced Concrete Beam Containing Iron Ore Tailings - Abubakar, Mahmud; Isiwu Aguwa, James; Ndakuta Kolo, Daniel; Yusuf, Abdulaziz; Sius Lawal, Sadiq (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2025)
This paper assesses the reliability of reinforced concrete beams incorporating IOT as a partial replacement for fine aggregates. An equation for the moment resistance capacity of IOT concrete beams was developed as well as the performance functions for the beam in flexure and shear conditions, providing a basis for evaluating structural performance under flexural loads. Reliability analysis was conducted using First Order Reliability Method to evaluate the safety indices of IOT concrete beam under flexure and shear conditions, based on stochastic modeling of load, material properties, and beam dimensions. Results showed that the reliability index (β) decreases with an increase in the load ratio, indicating higher failure risks under heavier loads. Sensitivity analysis also revealed that beam depth significantly influences reliability more than its length. The findings of the study can be used by engineers to optimize structural designs thus enhancing safety while addressing environmental concerns.